“Green” hydrogen, an alternative as an energy vector in the face of global warming. (LACCEI, 2024)
Decarbonization is a fundamental part of the global goals in the face of the climate threat. Greenhouse gas emissions are the main cause of global warming. The energy system is responsible for more than 70% of these emissions, and 12% corresponds to the transport of cargo and people through routes and roads. Argentina outlines its future towards a more environmentally friendly use of energy, and green hydrogen is called to be a fundamental player in sustainable mobility, and industrial uses, mainly due to its capacities to store energy in the face of the intermittency presented by the renewable sources. In particular, heavy and long-distance transport appears as a natural candidate to be supplied by hydrogen. Hydrogen as a fuel is an old idea, as in 1874 Jules Verne dedicated a paragraph of The Mysterious Island to it. "I believe that one day water will be a fuel, that the hydrogen and oxygen that constitute it, used alone or together, will provide an inexhaustible source of energy...", but the abundance of other resources, the difficulties to handle it safely and the lack of environmental awareness, they relegated it for 150 years.